Change of variables?

Calculus Level 4

0 1 0 1 x 2 ( 1 x 2 y 2 ) d y d x = ? \int_0^1 \int_0^{ \sqrt{ 1 - x^2} } ( 1 - x^2 - y^2 ) \, dy \, dx = \ ?

9 π 9 \pi π \pi π 9 \frac{ \pi }{9} π 8 \frac{\pi }{8}

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Discussions for this problem are now closed

Tony Sprinkle
Jan 4, 2015

The region we're integrating over is the quarter of the unit circle in the first quadrant of the Cartesian coordinate plane:

This integral is fairly difficult to evaluate using Cartesian coordinates, but changing to polar coordinates makes it much easier: 0 x 1 , 0 y 1 x 2 0 r 1 , 0 θ π 2 0 \le x \le 1,\quad 0 \le y \le \sqrt{1-x^2}\quad\Rightarrow\quad 0 \le r \le 1,\quad 0 \le \theta \le \frac{\pi}{2} 1 x 2 y 2 1 r 2 1 - x^2 - y^2\quad\Rightarrow\quad 1 - r^2 d y d x r d r d θ dy\: dx\quad\Rightarrow\quad r\: dr\: d\theta

Now we can evaluate: 0 π 2 0 1 ( 1 r 2 ) r d r d θ \int_0^{\frac{\pi}{2}} \int_0^1 (1 - r^2)r\: dr\: d\theta = 0 π 2 d θ 0 1 ( r r 3 ) d r =\int_0^{\frac{\pi}{2}} d\theta \int_0^1 (r - r^3)\: dr = π 2 ( r 2 2 r 4 4 ) 0 1 =\frac{\pi}{2} \left.\left(\frac{r^2}{2} - \frac{r^4}{4}\right)\right|_0^1 = π 2 ( 1 2 1 4 ) = π 8 =\frac{\pi}{2} \left(\frac{1}{2} - \frac{1}{4}\right) = \boxed{\dfrac{\pi}{8}}

Vighnesh Raut
Dec 31, 2014

L e t I = 0 1 0 1 x 2 ( 1 x 2 y 2 ) d y d x = 0 1 I 0 d x [ w h e r e I 0 = 0 1 x 2 1 x 2 y 2 d y ] N o w i n i n t e g r a l I 0 w e a r e i n t e g r a t i n g w i t h r e s p e c t t o y . S o , x i s c o n s t a n t i n I 0 Let\quad I=\int _{ 0 }^{ 1 }{ \int _{ 0 }^{ \sqrt { 1-{ x }^{ 2 } } }{ (1-{ x }^{ 2 }-{ y }^{ 2 } } ) } dy\quad dx\\ \quad \quad =\int _{ 0 }^{ 1 }{ { I }_{ 0 } } dx\quad \quad \quad \quad [where\quad { I }_{ 0 }=\int _{ 0 }^{ \sqrt { 1-{ x }^{ 2 } } }{ 1-{ x }^{ 2 } } -{ y }^{ 2 }dy]\\ Now\quad in\quad integral\quad { I }_{ 0 }\quad we\quad are\quad integrating\quad with\quad respect\quad to\quad y.\\ So,\quad x\quad is\quad constant\quad in\quad { I }_{ 0 }

I 0 = 0 1 x 2 1 x 2 y 2 d y = y y x 2 y 3 3 f r o m 0 t o 1 x 2 O n s i m p l i f y i n g w e g e t I 0 = 2 3 ( 1 x 2 ) 3 2 { I }_{ 0 }=\int _{ 0 }^{ \sqrt { 1-{ x }^{ 2 } } }{ 1-{ x }^{ 2 } } -{ y }^{ 2 }dy\\ \quad =y-{ yx }^{ 2 }-\frac { y^{ 3 } }{ 3 } \quad from\quad 0\quad to\sqrt { 1-{ x }^{ 2 } } \\ On\quad simplifying\quad we\quad get\quad \\ { I }_{ 0 }=\frac { 2 }{ 3 } { \left( 1-{ x }^{ 2 } \right) }^{ \frac { 3 }{ 2 } }

S o , I = 0 1 I 0 d x = 2 3 0 1 ( 1 x 2 ) 3 2 d x L e t x = s i n T d x = c o s T d T w h e n x 0 T 0 a n d x 1 T π 2 So,\quad I=\int _{ 0 }^{ 1 }{ { I }_{ 0 } } dx\\ \quad \quad \quad \quad =\frac { 2 }{ 3 } \int _{ 0 }^{ 1 }{ { \left( 1-{ x }^{ 2 } \right) }^{ \frac { 3 }{ 2 } } } dx\\ Let\quad x=sinT\\ \quad \quad dx=cosT\quad dT\\ when\quad x\rightarrow 0\\ \quad \quad T\rightarrow 0\\ and\quad x\rightarrow 1\\ \quad T\rightarrow \frac { \pi }{ 2 }

I = 2 3 0 π 2 c o s 3 T . c o s T d T = 2 3 0 π 2 c o s 4 T d T = 2 3 0 π 2 ( 1 + c o s 2 T 2 ) 2 d T = 1 6 0 π 2 1 + c o s 2 2 T + 2 c o s 2 T d T = 1 6 0 π 2 1 + ( 1 + c o s 4 T 2 ) + 2 c o s 2 T d T = 1 6 ( 3 T 2 + s i n 4 T 8 + s i n 2 T ) f r o m T = 0 t o π 2 = 1 6 ( 3 π 4 ) = π 8 \therefore \quad I=\frac { 2 }{ 3 } \int _{ 0 }^{ \frac { \pi }{ 2 } }{ { cos }^{ 3 } } T.cosT\quad dT\\ \quad \quad =\frac { 2 }{ 3 } \int _{ 0 }^{ \frac { \pi }{ 2 } }{ { cos }^{ 4 } } T\quad dT\\ \quad \quad =\frac { 2 }{ 3 } \int _{ 0 }^{ \frac { \pi }{ 2 } }{ { \left( \frac { 1+cos2T }{ 2 } \right) }^{ 2 } } dT\\ \quad \quad =\frac { 1 }{ 6 } \int _{ 0 }^{ \frac { \pi }{ 2 } }{ 1+{ cos }^{ 2 } } 2T+2cos2T\quad dT\\ \quad \quad =\frac { 1 }{ 6 } \int _{ 0 }^{ \frac { \pi }{ 2 } }{ 1+\left( \frac { 1+cos4T }{ 2 } \right) } +2cos2T\quad dT\\ \quad \quad =\frac { 1 }{ 6 } \left( \frac { 3T }{ 2 } +\frac { sin4T }{ 8 } +sin2T \right) \quad \quad from\quad T=0\quad to\quad \frac { \pi }{ 2 } \\ \quad \quad =\frac { 1 }{ 6 } \left( \frac { 3\pi }{ 4 } \right) \\ \quad \quad =\frac { \pi }{ 8 }

Well done ! Nice solution ! :D

Keshav Tiwari - 6 years, 5 months ago

thnk you ..

Vighnesh Raut - 6 years, 5 months ago

Use of gamma function make it less calculative

Yogesh Shivran - 6 years, 5 months ago

Yes ...realised it when saw others solutions .....

Vighnesh Raut - 6 years, 5 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...